IDENTIFIKASI STATUS KERUSAKAN TANAH UNTUK PRODUKSI BIOMASSA DI KECAMATAN TANJUNG PALAS TIMUR KABUPATEN BULUNGAN PROVINSI KALTARA - Surya Darma (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
The purpose of this study identify the parameters of the land degradation, in order to know the level of damage that occurs as a decision-making approach to the problem so that appropriate land productivity does not decreased, even increased as the cultivated area has a function for biomass production. The first step was to determine the potential indicative soil damage by overlaying the GIS-based digital maps, such as the map of soil type, slope, rainfall and land cover maps and then with RTRW/K. The result obtained that there are 4 classes of indicative damage land, they are very low, low, medium and high. The next focus was on the location of the high level damage potential, particularly in the village of Tanah Kuning, sub district of East Tanjung Palas. Result from field verification showed that effective soil depth (solum soil) > 150 cm, slope 15-25% and 6 soil samples taken for laboratory analyzes. The results of the evaluation of 10 land damage parameters showed that there are 2 parameters exceed a critical threshold, namely the composition of the fractions and pH (acidity) of the soil. The parameter exceeds a critical threshold pH found on all samples (6 samples), while the composition of the fraction was only one sample. Based on the relative frequency score status of soil damage is minor damage with the limiting factors are composition of sand fraction and the pH of acid soils. Remedial action against excessive sand composition was difficult because of permanent nature, while improving the soil pH (very acid) can be reduced with the application of agricultural lime and organic compost.